2010
DOI: 10.1007/s11627-010-9293-8
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of cell growth and cell division in maize (Zea mays L.) relevance of the conserved TOR signal transduction pathway

Abstract: Mechanisms that bring about coordination of cell growth and cell division in different organisms are biological events not yet clearly revealed. In maize, insulin effector of the phosphatidylinositol 3-kinase (PI3K)-target of rapamycin (TOR) signal transduction pathway in metazoan or an intrinsic maize growth factor similar to insulin has shown to regulate cell growth. This research has been undertaken to analyze the role of PI3K-TOR signal transduction pathway in maintaining coordinated regulation of cell gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
4
11
0
2
Order By: Relevance
“…Even though insulin has not been found in plants, it has been reported that this hormone and IGFs induce similar responses in plants; both effectors induce germination and growth of maize seeds (Sánchez de Jiménez et al , 1999; García-Flores et al , 2001) and accelerate growth of sunflower (Goodman and Davis, 1993) and Canavalia ensiformis seedlings (Oliveira et al , 2004); and in maize both ZmIGF and insulin enhance, by TOR pathway activation, the specific mobilization to polysomes and selective translation of mRNA related to protein synthesis, like S6rp, the translation initiation factor eIFiso4E (Dinkova et al , 2007) and ribosomal proteins (as has been demonstrated recently by microarray analysis; Jiménez-López et al , 2011). Also, it has been reported recently that ZmIGF/insulin induce mitogenic activation by increasing DNA synthesis in maize tissue cultures, as well as the mobilization into polysomes of mRNA coding for the proteins associated with the cell cycle, like PCNA and cyclin D1 (Sotelo et al , 2010) which participate in the G1–S transition, as mentioned earlier.…”
Section: Introductionmentioning
confidence: 67%
“…Even though insulin has not been found in plants, it has been reported that this hormone and IGFs induce similar responses in plants; both effectors induce germination and growth of maize seeds (Sánchez de Jiménez et al , 1999; García-Flores et al , 2001) and accelerate growth of sunflower (Goodman and Davis, 1993) and Canavalia ensiformis seedlings (Oliveira et al , 2004); and in maize both ZmIGF and insulin enhance, by TOR pathway activation, the specific mobilization to polysomes and selective translation of mRNA related to protein synthesis, like S6rp, the translation initiation factor eIFiso4E (Dinkova et al , 2007) and ribosomal proteins (as has been demonstrated recently by microarray analysis; Jiménez-López et al , 2011). Also, it has been reported recently that ZmIGF/insulin induce mitogenic activation by increasing DNA synthesis in maize tissue cultures, as well as the mobilization into polysomes of mRNA coding for the proteins associated with the cell cycle, like PCNA and cyclin D1 (Sotelo et al , 2010) which participate in the G1–S transition, as mentioned earlier.…”
Section: Introductionmentioning
confidence: 67%
“…16,17 Some land plants, however, lost this sensitivity. Among these plants are Arabidopsis and Vicia faba.…”
Section: Tor-binding Proteinsmentioning
confidence: 99%
“…These effects could be blocked by treatment with rapamycin, suggesting the involvement of TOR signaling in the response to IGF or insulin. 17 The translationally controlled tumor protein (TCTP) is an important component of the TOR signaling network. A large number of studies in various organisms have related TCTP to diverse cellular processes such as apoptosis, microtubule organization or ion homeostasis and several interacting proteins (e.g., Polo Kinase, Tubulin and Na + /K + -ATPase) were identified.…”
Section: Functional Importance Of the Tor Kinase In Plantsmentioning
confidence: 99%
“…Diferente evidencia sugiere que la insulina estimula el crecimiento en plantas como maíz y frijol (Sánchez de Jiménez et al, 1999;Santos, 2003) a una concentración de 1.23 nM. En maíz dicha concentración promovió la división y el crecimiento celular a través del reclutamiento a polisomas de transcritos como ciclina D y PCNA (Sotelo et al, 2010). En otros estudios sobre maíz, dicha concentración aceleró la germinación y la fosforilación de la proteína ribosomal S6 (Sánchez de Jiménez et al, 1999).…”
Section: Discussionunclassified
“…En cultivos de maíz sin restricción de fitorreguladores, también se ha descrito que la insulina estimula la proliferación celular a través ciclina D y PCNA (Sotelo et al, 2010). Por otra parte, se ha reportado que en cultivos BY-2 la ausencia de auxina conduce a una sincronización parcial con una proliferación acelerada después de la re-adición de auxinas al medio (Ishida et al, 1993).…”
Section: Discussionunclassified